Market power, dismissal threat and rent sharing: the role of insider and outsider forces in wage bargaining - Anabela Carneiro; Pedro Portugal (Institute for the Study of Labor (IZA), 2006)
One of the predictions of the insider-outsider theory is that wages will be higher in sectors (firms) with high labor adjustment costs/high turnover costs. This prediction is tested empirically in this study, using an insider-outsider model and a longitudinal panel of large firms in Portugal. The results revealed that firms where insider workers appear to have more market power tend to pay higher wages. In particular, we found that the threat of dismissal acts to weaken insiders' bargaining power and, consequently, to restrain their wage claims. Moreover, the results also showed that real wages in Portugal are downward rigid.
Keywords: J30; J31; 330; wages; market power; dismissal threat; rent sharing; system estimator; Lohnverhandlungen; Insider-Outsider-Modell; Theorie